Directive Illocutionary Acts in Venom: Let There Be Carnage Movie - Ni Ketut Ica Rahayuni; Putu Devi Maharani; Komang Dian Puspita Candra (CV Wahana Publikasi, 2022)
This study discussed the directive illocutionary act in Venom: Let There Be Carnage. It evaluates how all characters in the movie convey directive illocutionary acts. This study aims to find out the types of directive illocutionary acts. The data were collected using the observation method. The data is collected by watching the movie repeatedly while checking the conversation in the transcript and determining the utterance that contained a directive illocutionary act. Then, classify the utterance of the directive illocutionary act into three: command, request, and suggestions based on the theory by Kreidler (1998). In analyzing the data, the writer used the qualitative method. As a result, the writer found all types of directive illocutionary acts according to the theory from Kreidler (1998). There were 82 data found, and the most type of directive illocutionary act occurred was command with 51 data, request 23 data and suggestion 8 data.